Functional Redundancy and Divergence within the Arabidopsis RETICULATA-RELATED Gene Family(1)([W])([OA]) - Pérez-Pérez, José Manuel (American Society of Plant Biologists, 2013)
A number of Arabidopsis (Arabidopsis thaliana) mutants exhibit leaf reticulation, having green veins that stand out against paler interveinal tissues, fewer cells in the interveinal mesophyll, and normal perivascular bundle sheath cells. Here, to examine the basis of leaf reticulation, we analyzed the Arabidopsis RETICULATA-RELATED (RER) gene family, several members of which cause leaf reticulation when mutated. Although transcripts of RE, RER1, and RER3 were mainly detected in the bundle sheath cells of expanded leaves, functional RER3:GREEN FLUORESCENT PROTEIN was visualized in the chloroplast membranes of all photosynthetic cells. Leaf reticulation in the re and rer3 loss-of-function mutants occurred, along with accumulation of reactive oxygen species, in a photoperiod-dependent manner. A comparison of re and rer3 leaf messenger RNA expression profiles showed more than 200 genes were similarly misexpressed in both mutants. In addition, metabolic profiles of mature leaves revealed that several biosynthetic pathways downstream of pyruvate are altered in re and rer3. Double mutant analysis showed that only re rer1 and rer5 rer6 exhibited synergistic phenotypes, indicating functional redundancy. The redundancy between RE and its closest paralog, RER1, was confirmed by overexpressing RER1 in re mutants, which partially suppressed leaf reticulation. Our results show that RER family members can be divided into four functional modules with divergent functions. Moreover, these results provide insights into the origin of the reticulated phenotype, suggesting that the RER proteins functionally interconnect photoperiodic growth, amino acid homeostasis, and reactive oxygen species metabolism during Arabidopsis leaf growth.